The Comparison of Surface Dose in Vivo Dosimetry Using 3D-CRT and IMRT Technique on Breast Cancer Case - Wulandari, Sri; Ulya, Syarifatul; Diyona, Fiqi; Adrial, Rico; Prasetio, Heru (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
The aim of this study is to verify the adequacy of the surface radiation dose calculated by the Treatment Planning System (TPS) using 3DCRT and IMRT technique with the dose measured by the TLD-100, referring to the report of the American Association of Physicists in Medicine Task Group No.219 (AAPM-TG No.219). This research process began with annealing the TLD-100 at the Research Center for Safety Technology Metrology and Nuclear Quality of the National Innovation Research Agency (PRTKMMR-BRIN), followed by scanning the TLD-100 on the surface of the phantom plate using a CT simulator. In addition, the TLD-100 was calibrated with different radiation doses (0; 20; 50; 80; 100; 150; 200; 250; 370) cGy. Verification of the surface radiation dose was performed by calculating the TPS surface dose by Patient Specific Quality Assurance (PSQA) and comparing it with the dose measured by the TLD-100. The result is Radiation techniques such as IMRT are more conformal than 3D-CRT because they precisely control dose intensity, making the TLD dose in IMRT closer to TPS. Differences in detector types such as TLD also affect the results of radiation dose measurements. Continuous assessment of patient dose is important for the safety of radiation therapy.